2021
DOI: 10.3390/agriculture11111090
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption of Agricultural Machinery by Chinese Maize Farmers

Abstract: As the major labor force has shifted from rural areas to cities, labor shortages in agricultural production have resulted. In the context of technical progress impact, and depending on farm resource endowments, farmers will choose effective labor saving technology such as machinery to substitute for the missing manual labor. The reasons behind farmers’ adoption of machinery technology are worth exploring. Therefore, this study uses 4165 Chinese maize farmers as the target group. Multivariate probit models were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…In contrast, in other provinces with higher pesticide expenditure, the AMS rate is relatively low. Similarly, the results of Quan and Doluschitz indicate that the maize farmers in the northeast and northern regions of China are more likely to use agricultural machinery than in other areas ( 21 ).…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, in other provinces with higher pesticide expenditure, the AMS rate is relatively low. Similarly, the results of Quan and Doluschitz indicate that the maize farmers in the northeast and northern regions of China are more likely to use agricultural machinery than in other areas ( 21 ).…”
Section: Resultsmentioning
confidence: 92%
“…Therefore, it is essential for entrepreneurs and farmers to consider the long-term benefits of any technology investment [68]. Moreover, economies of scale can also positively influence the adoption of digital technologies [58]. There is a positive relationship between yearly income and the use of Agriculture 4.0 technologies [63].…”
Section: Economic and Environmental Factorsmentioning
confidence: 99%
“…Farmers with larger farms exhibit greater enthusiasm towards the adoption of smart technologies, as they can afford to bear the entire costs and relative risks [39,40]. In contrast, small-scale farmers often struggle to adopt innovative technologies due to a scarcity of investment capital or knowledge [43], including those from family farms [58]. Small and medium farmers are likely to manage farm operations in a traditional manner and may not require the utilisation of 4.0 technologies for farm management [62].…”
Section: Farm-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The empirical literature on agricultural mechanization mainly focuses on the factors that aff ect agricultural mechanization and its socio-economic impacts. Studies have shown that household-level influencing factors of agricultural mechanization include age and education , total household assets (Mottaleb et al, 2016), technical training (Nakano et al, 2018), and off -farm employment opportunities of rural householders , as well as the availability of arable land (Quan and Doluschitz, 2021). Regional-level influencing factors include physical geography (Ullah and Anad, 2007), credit availability , road density (Mottaleb et al, 2016), labor costs (Zheng and Xu, 2017), labor migration (De Brauw and Rozelle, 2008), and the price of agricultural technology (Mottaleb, 2018).…”
Section: Literature Review and Theoretical Analysismentioning
confidence: 99%